Ethics in Educational Evaluation and Assessment (Ethical Principles in Educational Evaluation and Assessment from the Perspective of Fairness, Objectivity, and Privacy) - Abdul Rahman Sidik; Dina Hermina; Nuril Huda (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to examine the ethical principles in educational evaluation and assessment and the application of ethical evaluation in the context of Islamic education. The research employs a qualitative approach through literature reviews and interviews with Islamic Education teachers at SMKN 3 Banjarmasin, analyzing data from books, journals, and digital sources. The findings reveal that evaluation and assessment are crucial components in education for measuring student achievement and improving educational quality. These practices must adhere to ethical principles such as fairness, objectivity, and privacy. Fairness ensures that all students are treated equally without discrimination through transparent and unbiased evaluation tools. Objectivity emphasizes assessment based on concrete data, avoiding personal bias, and using clear assessment rubrics. Privacy involves protecting student data, limiting access to authorized parties, and respecting students’ rights to keep their information confidential. In Islamic education, these principles reflect the moral values of the Qur’an regarding justice and respect for individuals. Ethical evaluation fosters an inclusive learning environment and supports students’ holistic development.